Clathrin in Chara australis: Molecular Analysis and Involvement in Charasome Degradation and Constitutive Endocytosis - Hoepflinger, Marion C.; Hoeftberger, Margit; Sommer, Aniela; Hametner, Christina; Foissner, Ilse (Frontiers in Plant Science, 2017)
Charasomes are convoluted plasma membrane domains in characean green algae. They are known to form in response to light via secretion of trans-Golgi network (TGN) vesicles and local inhibition of endocytosis. Charasomes are involved in the acidification of their aqueous environment, thereby facilitating photosynthesis-dependent carbon uptake. Charasome formation is reversible to allow cells to adapt to different light conditions. Here we show that darkness-induced degradation of charasomes involves the formation of coated pits and coated vesicles. The darkness-induced degradation of charasomes can be inhibited by 1-2 µM ikarugamycin (IKA), which is considered to be a specific inhibitor of clathrin-dependent endocytosis. At a much higher concentration (100 µM), IKA also significantly reduces the internalization of styryl dyes, indicating uptake via clathrin-coated vesicles. We are the first to present evidence, based on fine structure investigation, that IKA does not interfere with the formation of clathrin coat, but inhibits the detachment and/or further processing of coated vesicles. Both charasome degradation and constitutive endocytosis are also significantly inhibited by sterol complexing agents (methyl-ß-cyclodextrin and filipin). The absence of an additive effect, when applied together with IKA, suggests that charasome degradation and constitutive endocytosis (measured via styryl dye uptake) is not inhibited due to membrane retrieval via lipid rafts, but due to clathrin coat formation requirement of a specific set of sterols. Analysis of Chara australis clathrin proteins revealed two heavy chains and several light chains with sequence peculiarities, suggesting functional and/or species specific differences. The data obtained indicate that clathrin plays a central role not only in constitutive endocytosis but also in the degradation of charasomes, thereby representing a valuable system for studying targeted exo- and endocytosis.